Transformasi Pekerja Informal ke Arah Formal: Analisis Deskriptif dan Regresi Logistik - Purnama Sari, Nindya (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 1, Februari 2016 (pp. 1 - 88)DO - 10.24843/JEKT.2016.v09.i01.p03)
Eventhough National Labour Force Survey (Sakernas) August 2014 shown a low open unemployment rate in Badung Regrency, that is 0.48 percent, but it cannot describe people ability to fulfill their daily needs. Quality of job effects quality of life. A weak relationship between employee and employment aggravates the quality of informal job. By finding information about characteristics of people who work in informal sectors and also its contribution and relationship to their decision to work in informal sector, hopes can help in formulatingthe employment policies. To seek further this information, we use Sakernas August 2014 of Badung Regency data and matching with individual characteristics collected by Employment Office (Disnakertrans) of Badung Regency. A descriptif analysis show that a transformation worker from formal to informal in Badung Regency has been running. Amout of informal worker in Badung Regency is decreased year by year. In the other hand, the higher number of mobility worker form formal sector to informal sector restrains the transformation. Furthermore, logistic regression analysis shown that women employee with a lower education and an older age tend to work in informal sector. Apparently, economy needs of married people does not give a significant contribution in deciding to work in informal sector.
Keywords: employment, formal, informal, transformation